2023
DOI: 10.60072/ijeissah.2023.v1i02.003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Interpersonal Skills of the School Principals in Optimizing Positive School Climate: A Concept Paper

Tahir Mehmood,
Sahar Taresh,
Datin Hafizah
et al.

Abstract: Fostering a positive school climate is an essential aspect of school improvement. Research has shown that the interpersonal skills of school principals play a crucial role in optimizing school climate. This concept paper aims to develop a conceptual framework that utilizes the current literature on the role of the principal's interpersonal skills in optimizing positive school climate. The literature review focuses on specific interpersonal skills such as communication, trustworthiness, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The Broader Impact on School Culture and Environmental Awareness: Effective communication strategies have a profound impact on shaping school culture and fostering environmental awareness. Mehmood, T., Hassan, D. H. C., & Taresh, S. (2023) suggests that a well-communicated climate change education program can contribute to a culture of environmental responsibility among students. Principals, by championing these initiatives, contribute to creating an ethos where sustainability is ingrained in the school's identity.…”
Section: Implications and Recommendations A Implications For Educatio...mentioning
confidence: 99%
“…The Broader Impact on School Culture and Environmental Awareness: Effective communication strategies have a profound impact on shaping school culture and fostering environmental awareness. Mehmood, T., Hassan, D. H. C., & Taresh, S. (2023) suggests that a well-communicated climate change education program can contribute to a culture of environmental responsibility among students. Principals, by championing these initiatives, contribute to creating an ethos where sustainability is ingrained in the school's identity.…”
Section: Implications and Recommendations A Implications For Educatio...mentioning
confidence: 99%
“…Moreover, fostering a positive school climate is an essential aspect of school improvement. Research has shown that the school heads' interpersonal skills play a crucial role in optimizing school climate [56]. In fact, the results of their study suggested that effective leadership or supervision is characterized by trustworthiness, empathy, problem-solving, and effective interpersonal skills, which contribute to a positive organizational climate and enhanced learning outcomes for teachers and students.…”
Section: She Places An Emphasis On Open Communication and Collaborati...mentioning
confidence: 99%
“…Beyond the traditional emphasis on medical knowledge acquisition and technical proficiency, there is a growing acknowledgment of the pivotal role interpersonal skills play in shaping competent and compassionate healthcare practitioners. As medical schools strive to produce well-rounded professionals, the integration of interpersonal skills into the curriculum emerges as a crucial aspect of this transformative journey Mehmood, T., Hassan, D. H. C., & Taresh, S. (2023).…”
Section: Introductionmentioning
confidence: 99%
“…Importance of Collaboration, Support, and Effective Communication: Collaborative learning, faculty support, and effective communication within the medical school environment contribute to a positive and conducive climate for learning and professional development Mehmood, T., Hassan, D. H. C., & Taresh, S. (2023). Students who perceive a supportive and collaborative atmosphere are likely to thrive academically and personally (Howell et al, 2017;Côté & Lopes, 2014).…”
Section: Introductionmentioning
confidence: 99%